Assessment of Genetic Purity of Inbred Strains of Mice using Microsatellite Markers - Raut, Sachin; Singh Chopra, Bhupinder; Khatri, Neeraj (Toxicology International, 2021)
Monitoring of genetic make-up of inbred strains of mice is one of the most essential and basic requirements to assure the continued purity and homogeneity of the strains. It further helps in maintaining phenotypic characteristics of mice strain, which in turn, ensures the reproducibility of research outcomes between the group of mice and over time. In the present study, the phenotypic and genotypic characteristics of various inbred strains of mice maintained in our Animal Facility were assessed to ascertain their purity. The mice exhibited strain-specific phenotypic characters and skin coat colours in accordance with the published profile of the specific strains. The average litter size of C57BL/6 and BALB/c mice, the most commonly used strains of mice, was calculated over different generations and found to be 5 to 6.6 and 4 to 6, respectively. For checking the genetic purity of mice, more than 1700 tissue samples (ear punched tissue) were collected from various strains of mice. Genomic DNA was isolated from the tissue samples and subjected to PCR-based microsatellite analysis. Amplified PCR products of genomic DNA of tested mice showed identical amplicon base-pair length as per the published profile in the MGI database, indicating the purity and uniformity of the mice.